WAYS OF ORGANIZING AN INNOVATIVE EDUCATIONAL ENVIRONMENT IN THE NEW UKRAINIAN SCHOOL - Oliiar, Mariia; Kopchak, Liliia; Dovgyi, Oleh (Mountain School of Ukrainian Carpaty, 2024)
Relevance of the research is related to the methodological and technological imperfections of the educational process in educational institutions, its fragmentation, and the insufficient level of psychological and pedagogical readiness of teachers for innovative changes in educational work in the context of the modern information society and the large-scale war in Ukraine. The aim of the article is to reveal the theoretical and methodological foundations for organizing an innovative educational environment in general secondary education institutions. The author analyzed scientific sources concerning the problems of educating youth and various aspects of developing innovative processes in education. The main problems in the educational and upbringing space in Ukraine are analyzed. It is noted that innovations, under current conditions, are becoming one of the most important directions of educational activities in educational institutions; however, new educational practices are being implemented slowly and are often carried out without consideration of changes in social and regional conditions. A new format of educational work is characterized, defining the personal development of students as the primary goal of education in all educational institutions. Factors affecting the quality of the educational process have been identified. The interpretations by Ukrainian scholars of the concepts of «innovation in education,» «innovativeness,» «innovative process,» and «innovative educational environment of general secondary education institutions» are highlighted. The innovative educational environment of the New Ukrainian School (NUS) is characterized, and pathways for its creation as an innovative educational interaction between teachers and students on a subject-subject basis are outlined. The professional mission of NUS teachers in educational work is defined as the pedagogical support of the process of individual formation and development of students’ personalities during their school education, including forecasting, organization, control, and analysis of the daily lives and activities of schoolchildren. It is emphasized that modern technologies are at the core of developing a new educational system, the main principles for selecting which are prospectivity, democratic nature, humanistic orientation, integrativeness, realism, wholeness, manageability, economy, and relevance. A values-based approach to education is defined as the most important condition for the personal development of students, realized through the construction of the structure of the value-oriented educational space of a modern educational institution. Education is recognized as the leading priority in the educational space, the expected results of which can only be achieved through updating its content, corrected to new goals and benchmarks of competency-based education. Keywords: general secondary education institution,